Incidência de TB diagnosticada no pronto-atendimento de um hospital escola na região sudeste do Brasil Incidence of TB diagnosed in the emergency room of a teaching hospital in southeastern Brazil - Silvana Spíndola de Miranda; Ana Rita de Paiva Toledo; Simone Rodrigues Ribeiro; Izabela Magalhães Campos; Petra Maria de Oliveira Duarte Sthur; Afrânio Lineu Kritski (Jornal Brasileiro de Pneumologia, 2009)
Neste trabalho, analisamos o número de casos de TB em um pronto-atendimento (PA) e o perfil de sensibilidade das cepas de Mycobacterium tuberculosis. Pacientes atendidos no Hospital das Clínicas, em Belo Horizonte (MG), foram selecionados. Entre 2002 e 2005, 240 pacientes com TB foram identificados. Destes, 117 (48,7%) foram diagnosticados no PA, 72 (61,5%) com baciloscopia positiva. Testes de sensibilidade foram realizados em 90 cepas, sendo 80 (89%) sensíveis, 9 (10%) resistentes e 1 (1%) multirresistente. A incidência de baciloscopia positiva e de TB resistente foi elevada, o que demanda uma adoção urgente de medidas de controle de TB no PA. In this study, we analyzed the number of TB cases in an emergency room (ER) and the susceptibility profile of Mycobacterium tuberculosis strains. Patients were selected from among those treated at the Hospital das Clínicas, in the city of Belo Horizonte, Brazil. Between 2002 and 2005, 240 TB patients were identified. Of those, 117 patients (48.7%) were diagnosed in the ER, 72 (61.5%) presenting positive sputum smear microscopy. Drug susceptibility testing was carried out in 90 strains, of which 80 (89%) were sensitive, 9 (10%) were resistant, and 1 (1%) was multidrug resistant. The incidence of positive smear sputum microscopy and resistant TB strains was high, which calls for the immediate adoption of TB control measures in the ER.